The Guts to Fight Back - Terre Blanche, Martin; Hamber, Brandon (PINS-Psychology in Society, 2026)
Anita Craig is worried about many things The over-use of unstructured interviews misconceptions regarding the sex-lives of homosexuals, people who say "in my experience the importance of this cannot be underestimated" (sic), the hairstyles of black female TV continuity announcers, and so forth. We all have similar gripe lists and labour to convince others of the importance and deep coherence of what to them may seem arbitrary and bizarre. Craig uses a well-worn strategy to achieve this. First, she invokes the master signifier of a future-directed rationality set off against all the various forms of soppy emotionality, subjective gut feelings and unthought-through prejudices that supposedly characterise "life in general in South Africa nowadays". Second, she declares herself exempt from the injunction against subjectivity, speaking in the register of authoritative but highly subjective self-disclosure. Thus we are told again and again what Craig believes, finds attractive, agrees with, is enticed by worries about, feels unsure about, thinks, considers to be a "fine analysis" intuits, and so on, and paradoxically these intuitions all centre around a conviction that such subjective assertions do not constitute proper grounds for knowledge.